Bank Capital : Lessons From the Financial Crisis - Merrouche, Ouarda (IMF Working Papers; Working Paper ;, 2010)
Using a multi-country panel of banks, we study whether better capitalized banks experienced higher stock returns during the financial crisis. We differentiate among various types of capital ratios: the Basel risk-adjusted ratio; the leverage ratio; the Tier I and Tier II ratios; and the tangible equity ratio. We find several results: (i) before the crisis, differences in capital did not have much impact on stock returns; (ii) during the crisis, a stronger capital position was associated with better stock market performance, most markedly for larger banks; (iii) the relationship between stock returns and capital is stronger when capital is measured by the leverage ratio rather than the risk-adjusted capital ratio; (iv) higher quality forms of capital, such as Tier 1 capital and tangible common equity, were more relevant.